NPK fertilization experiments on corn in Minas Gerais state - Bahia, Francisco; Magnavaca, Ricardo; Santos, Hélio L. dos; Silva, Jairo; Bahia Filho, Antônio F.C.; França, Gonçalo E. de; Murad, Antônio M.; Macêdo, Álvaro A. de; Silva, Tácito; Filho, Edgar Cunha (Pesquisa Agropecuaria Brasileira, 2014)
NPK field experiments on corn were carried out in the State of Minas Gerais during 1967/70 under an agreement signed by IPEACO/BNDE/ANDA. The experiments, 23 in total, were conducted at seven different sites in Minas Gerais: Patos de Minas, Guaranésia, Pains, Passos, Guaxupé, Rosário de Minas and Coronel Pacheco. Soils in all experimental areas were chemically analysed and classified. The experimental design used was 3x3x3 factorial with interaction for NPK totally confounded, group W. Fertilizers were applied at rates of 0, 60, 120 kg N/ha; 0, 60, 120 kg P2O5/ha; 0, 30, 60 kg K2O/ha. Hmd 6999 B double cross hybrid corn was used in all experiments. Analysis of variance and the Mitscherlich method of economic analysis were used in interpreting the results. For the analysis, results from the same great soil group were combined. In applying the Mitscherlich method the average prices for corn and fertilizers in 1970, published by "Departamento de Estudos Rurais" of the Secretaria de Estado da Agricultura de Minas Gerais", were used. The experiments on the "Roxo" Eutrofic Latosol, the Reddish-brown Lateritic soil, the Yellow Mediterranian soil and the Aluvial soil show significant effects for nitrogen, with economic returns from 150, 75, 73 and 143 kg N/ha, respectivelly. Even though the experiments on the Yellow-red podzolic intergrade, the Reddish-brown Lateritic soil, the Dark Red Latosol (Cerrado phase) and the Yellow-red Podzolic Latasol showed significant effects for nitrogen, conditions were not provided for estimating economic levels. The experiments on the Reddish-brown Lateritic soil, the Yellow-red Mediterranian soil, the Dark Red Latosol (Cerrado phase), and the alluvial soil responded significantly to phosphorus, economic levels were 113, 81, 111, and 97 kg P2O5/ha, respectively. A significant effect for phosphorus was found for the Yellow Red Podzolic. However, it was impossible to check the economic response level on this soil. The experiment on the Yellow Red Podzolic Latosol responded significantly to potassium and the economic level was 89 kg K2O/ha. Responses obtained with phosphorus fertilization correlate with soil analysis for this element.